2018
DOI: 10.1097/mlr.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Primary Care Provided to Medicare Beneficiaries by Nurse Practitioners and Physicians

Abstract: The quality of primary care varies by clinician type, with different strengths for PCNPs and PCMDs. These comparative advantages should be considered when determining how to organize primary care to Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 24 publications
0
108
0
Order By: Relevance
“…Prior studies suggest that provider characteristics (eg, gender, type), as well as practice size and network affiliation can influence the quality of primary care delivered. 33 - 37 As such, to balance practice-level characteristics, covariates included count of each clinician type, proportion of clinicians that was female, and network affiliation. We then calculated inverse probability of treatment weights (IPTWs) using the estimated propensity scores.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies suggest that provider characteristics (eg, gender, type), as well as practice size and network affiliation can influence the quality of primary care delivered. 33 - 37 As such, to balance practice-level characteristics, covariates included count of each clinician type, proportion of clinicians that was female, and network affiliation. We then calculated inverse probability of treatment weights (IPTWs) using the estimated propensity scores.…”
Section: Methodsmentioning
confidence: 99%
“… 21 , 34 , 35 Studies of transitional care have focused on the post-acute care population transitioning from one setting to another, with NPs providing transitional care supplemental to the care delivered by the primary care providers. 20 , 36 Although substantial evidence has shown that NPs provide quality of care similar to that of physicians, 37 , 38 even with medically complex patients 39 most of these studies have focused on acute care 40 or ambulatory care, 41 , 42 and these findings are not generalizable to care provided in a patient's home environment which presents unique challenges. 34 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Primary care physicians may play an especially important role in managing an aging population with multiple complex conditions. 10,11 In the early 1970s, internal medicine (IM) primary care residency programs and tracks were developed to help produce more primary care internists. 12 Recent evidence suggests that graduates of IM primary care programs are twice as likely to pursue primary care careers than their categorical IM resident colleagues.…”
Section: Introductionmentioning
confidence: 99%